2022
DOI: 10.1002/cbdv.202100956
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Evaluation of 1,3,4‐Oxadiazole‐Isobenzofuran Hybrids as Antimicrobial and Anticancer Agents

Abstract: In drug discovery, the hybridization of bioactive pharmacophores is a powerful tool for targeting enzymes involved in cancer and microbial cell growth. A combination of 1,3,4‐oxadiazole and isobenzofuran may improve the antitumor and antimicrobial properties of the hybrid molecules. A series of hybrid molecules having 1,3,4‐oxadiazole and isobenzofuran were synthesized and structural characterization was done by FT‐IR, 1H‐NMR, 13C‐NMR, and mass spectrometry. Molecular docking studies were performed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Among the derivatives evaluated, compound 289 revealed highest activity with IC 50 value of 4.15 μM. [84]…”
Section: Anticancer Agentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among the derivatives evaluated, compound 289 revealed highest activity with IC 50 value of 4.15 μM. [84]…”
Section: Anticancer Agentsmentioning
confidence: 95%
“…The compounds show excellent anticancer activity against HCT 116 cell lines. Among the derivatives evaluated, compound 289 revealed highest activity with IC 50 value of 4.15 μM [84] …”
Section: Biological Activitiesmentioning
confidence: 99%
“…Further studies revealed that the incorporation of isobenzofuran or thioether between indole and 1,3,4-oxadiazole moieties could not improve the activity. [77,78]…”
Section: Indole/isatin-azole Hybridsmentioning
confidence: 99%